2019
DOI: 10.3390/cryst9110589
|View full text |Cite
|
Sign up to set email alerts
|

PbI2 Single Crystal Growth and Its Optical Property Study

Abstract: In this work, we used the chemical vapor transport (CVT) method to grow PbI2 crystals using iodine as a self-transporting agent. The crystals’ structure, composition, and uniformity were confirmed by X-ray diffraction (XRD) and electron probe microanalysis (EPMA) measurements. We investigated the band gap energy using absorption spectroscopy measurements. Furthermore, we explored the temperature dependence of the band gap energy, which shifts from 2.346 eV at 300 K to 2.487 eV at 20 K, and extracted the temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 32 publications
4
21
0
4
Order By: Relevance
“…2d testifies a layered structure of the crystals. The appropriate angle, 120°, is characteristic for hexagonal crystallites, which has also been observed for the PbI 2 crystals grown by a chemical-steam transport under the condition that iodine is a self-transporting agent [27].…”
Section: Resultssupporting
confidence: 52%
“…2d testifies a layered structure of the crystals. The appropriate angle, 120°, is characteristic for hexagonal crystallites, which has also been observed for the PbI 2 crystals grown by a chemical-steam transport under the condition that iodine is a self-transporting agent [27].…”
Section: Resultssupporting
confidence: 52%
“…We confirmed the crystal structure by Rietveld fitting the XRPD pattern on the base of the structure published by Ni et al, 21 discovering at the same time the presence of a byproduct identified by some residual peaks, which we suspect to be PbI 2 nanosheets or flakes on the basis of the match with published XRPD data (Figure S32 and Table S9). 78,79 We take the remarkable resemblances between the XRPD patterns of Pb 4 S 3 I 2 and Pb 4 S 3 Br 2 as an additional proof of the close similarity of the two structures.…”
Section: ■ Results and Discussionmentioning
confidence: 91%
“…al., 21 discovering at the same time the presence of an byproduct identified by some residual peaks ( Figure 7c, top pattern), which we suspect to be PbI2 nanosheets or flakes on the base of the match with published XRDP data (see also Figure S8). 77,78 We take the remarkable resemblances between the XRPD patterns of Pb4S3I2 and Pb4S3Br2 as an additional proof of the close similarity of the two structures.…”
Section: Preliminary Investigation Of Iodide and Chloride-based Ncsmentioning
confidence: 90%
“…On the one hand, the transmission capacity of the raw material atmosphere is limited. On the other hand, the quartz tube's axial and radial temperature gradients are large [14,15]. As a result, the environment of the raw material atmosphere during crystal growth is uneven and unstable, and the continuity of crystal growth cannot be maintained.…”
Section: Introductionmentioning
confidence: 99%